The Influence of Global Ideas on Environmentalism and Human Rights : World Society and the Individual - Hadler, Markus (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book explores whether individual attitudes and behaviors are swayed by global developments in a world increasingly populated by organizations, treaties, and other institutions that focus on environmentalism and human rights. It uses the sociological approach of World Society theory to investigate the effects of global ideas on individual environmentalism, xenophobia, and homophobia while drawing its data from a variety of international public opinion surveys. The Influence of Global Ideas on Environmentalism and Human Rights questions the dominant narrative of World Society related research as a positive influence of global ideas on various outcomes. Hadler demonstrates the complexity of this issue through empirical analyses revealing mixed trends in attitudes and behaviors from around the world. This book will be of interest to academics seeking to critically engage with World Society theory through two of its core topics: human rights and environmentalism.
Keywords: Social sciences.; Human rights.; Social structure.; Social inequality.; Environmental sociology.; Social justice.; elektronické knihy; electronic books